COMPARISON BETWEEN THE EFFECT OF AN ACUTE RESISTANCE EXERCISE SESSION WITH INTENSE AND LIGHT LOAD CIRCUIT METHOD ON BLOOD PRESSURE (Fiep Bulletin - online, 2011)
Introduction: The literature reports that after a resistance exercise session a hypotensive effect can be observed, which could contribute to the treatment of hypertension. However, there is still controversy about the type, intensity and duration of exercise to achieve this goal safely. Objective: This study aims at comparing the behavior of blood pressure after 60 minutes of recovery from a resistance exercise session in the circuit method with 40% and 80% of 1RM. Methods: The participants were 12 normotensive men aged 24,9 ± 2,43; body mass 71,68 ± 5,18kg; height 173 ± 0,16 in; IMC 23,83 ± 1,60 kg/m2 and % fat of 16,84±2,99. The volunteers attended the laboratory for four trial sessions of weight training on alternated days: 1 – maximum load (1-RM) in six exercises (leg extension, bench press machine, leg curl and rowing machine), 2, 3 and 4 – in random order for the experimental sessions: 3 circuit of 8 repetitions of resistance exercise at 80% 1-RM session, 3 circuit of 16 repetitions of resistance exercise at 40% 1-RM session and a control (CONT) without performing the exercise. The variables measured at rest and after the experimental sessions, within 60 minutes of recovery were systolic blood pressure (SBP) and diastolic. Data were analyzed using descriptive statistics with mean and standard deviation. Two-way ANOVA for repeated measures was applied for comparison of results within and between experimental sessions with Post-hoc de Tukey test (p < 0,05). The software Statistics for Windows 6.0 was employed. Resuslts: There was no increase in SBP and DBP in volunteers evaluated after the exercise sessions, as well as hypotensive effect was not observed during the recovery period. However, there was significant reduction in DBP at 30 min compared with the value at the end of the exercise. Conclusion: It is concluded that there was no significant difference in blood pressure between sessions of resistance exercise in loads of 40 and 80% of 1-RM, as well as no hypotensive effect was observed.
Keywords: resistance exercise; blood pressure; post-exercise hypotension